Two practical strategies for developing resultant muscle torque production using elastic resistance device - Aboodarda, S.J.; Yusof, A.; Abu Osman, Noor Azuan; Ibrahim, Fatimah (2011)
This investigation was conducted to quantify and compare Resultant Muscle Torque (RMT) pattern in quadriceps muscle using elastic resistance training device. Sixteen subjects completed 8-RM seated knee extension by elastic tubing with original length (E0) and elastic tubing with 30 decrement of original length (E30). Every repetition was partitioned into 6 phases (3 concentric and 3 eccentric) and mean value for external force and acceleration were calculated and synchronized for every phase of lifting. The magnitude of Resultant Muscle Torque was calculated based on the equation recommended by Enoka (2002) for dynamic motions. the RMT values among various exercise types phases demonstrated significantly higher value for E30 compared with E0 (all P < 0.05). This is except in the 3 rd and 4 th phases of contraction which no significant difference observed between E0 and E30. Accordingly, the magnitude of increasing RMT in phase 1 (2.6 ) and phase 6 (3.98 ) for E30 compared with E0 supported the effectiveness of two applied strategies in developing muscle torque production in ER exercises. Â© 2011 Springer-Verlag.